Intertemporal prosocial behavior: a review and research agenda - Persson, Emil; Tinghög, Gustav; Västfjäll, Daniel (Frontiers in Psychology, 2024)
Research on intertemporal and prosocial decisions has largely developed in separate strands of literature. However, many of the decisions we make occur at the intersection of these two dimensions (intertemporal and prosocial). Trust is an example, where a decision today is made with the expectation that another person will reciprocate (or betray) later. A new literature is emerging to explore the role of time in these types of situations, where time and social considerations are intertwined. In many cases, time introduces (or magnifies) an element of uncertainty about future outcomes and utility that people need to deal with – what will happen, how good will it be, how will it feel. We review this emerging literature on intertemporal prosocial decision-making and discuss how new research can fill existing knowledge gaps.